Mergers and Acquisitions: Evaluation of Impacts on Firm Performance – The UK Evidence - Wang, Dian (2014)
The number of mergers and acquisitions are rapidly increasing in emerging market in recent years and M&As have become the most important and practical corporate tool to pursue firm’s external growth. M&A activities not only can expand market shares but also create value for companies and shareholders. This paper investigates the impact of mergers and acquisitions on the stock returns of acquiring firms in the UK market for the period between 2001 and 2005. This research firstly introduces some concepts of M&A, such as definitions, types, motivations and so on. Then it reviews some relevant findings of previous empirical works. Furthermore, event study is regard as the main methodology of this study and the research is conducted based on two even windows: five-day (-2, +2) and eleven-day (-5, +5). Besides, we use cross-sectional regression to examine which factor would be the most influenced determinant on bidder’s performance. Our result reveals that bidding firms on average receive positive abnormal returns around the announcement date. In terms of targets status, the evidence shows that acquisitions generate statistically significant positive returns to bidders when they acquire private and subsidiary targets while insignificant negative returns when they acquire public targets. By analysing the sub-samples of different factors (i.e. relative size, acquirer size, methods of payment, acquirer’s book-to-market ratio and industry), we find that the most influenced factors are cash payment and relative size of acquisitions, and both of them have positive effect on firm’s performance during M&A activities.